Humanismo e ontologia em Merleau-Ponty - Bruno Victor Parreiras Soares Melo (2018)
In this work we will seek to understand the ontological foundations of Merleau-Ponty's political philosophy. To do so, we will go through the different approaches of the human in his work, going through the initial texts that were marked by the reading of Karl Marx and the development of his phenomenology, until we arrive in his late texts where the rupture with Marxism occurs. At this moment, a new conception of the human is born in his philosophy from the notion of institution that we believe to be the expression of the MerleauPontyana reading of Machiavelli and his humanism.